The Role Of Islamic Religious Education In Shaping Students' Attitudes Toward The Kajang Customary Beliefs - Karadona, Rosika Indri; Rahmawati, Rahmawati; Arsyad, Yolandika; Mudatsir, Mudatsir (Journal of Indonesian Progressive Education, 2026)
Islamic Religious Education (PAI) plays a strategic role in shaping students' religious attitudes, especially in the context of communities with a strong traditional belief system. This research aims to analyze the role of Islamic Religious Education in shaping students' attitudes toward the Kajang customary beliefs at SMA Negeri 13 Bulukumba. This research uses a qualitative approach with a case study type. The subjects of the research include students from the Kajang indigenous community as well as Islamic Religious Education teachers. Data collection techniques were carried out thru in-depth interviews, participatory observation, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing and verification, with data validity maintained thru source and technique triangulation. The research results show that Islamic Religious Education at SMA Negeri 13 Bulukumba plays an important role in shaping students' religious, tolerant, and moderate attitudes. Islamic Religious Education (PAI) not only serves as a means of transferring religious knowledge but also as a medium for the internalization of moral and spiritual values implemented in the daily lives of students. On the other hand, the Kajang customary beliefs based on the pasang ri Kajang are maintained as a cultural identity and a guideline for the community's way of life. This research found a pattern of coexistence and value dialog between Islamic teachings and traditional beliefs, where students are able to respect customs as local wisdom without neglecting the principles of Islamic teachings. Thus, contextual and culturally sensitive Islamic Religious Education has proven capable of shaping students' characters to be both religious and cultured.